2014
DOI: 10.1002/cne.23558
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate‐induced photoreceptor death and retinal remodeling in rats

Abstract: Many common causes of blindness involve the death of retinal photoreceptors, followed by progressive inner retinal cell remodeling. For an inducible model of retinal degeneration to be useful, it must recapitulate these changes. Intravitreal administration of adenosine triphosphate (ATP) has recently been found to induce acute photoreceptor death. The aim of this study was to characterize the chronic effects of ATP on retinal integrity. Five-week-old, dark agouti rats were administered 50 mM ATP into the vitre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 91 publications
6
31
1
Order By: Relevance
“…Retinal ganglion cells appeared well conserved. These features are consistent with mid-to-late stage remodeling events reported in ATPinjected cat and rat retinae 24 and other models of retinal degeneration. 7,64,65 When local variations in retinal layer thickness, gliosis, and ganglion cell density were correlated with individual electrode thresholds in the implanted degenerate and control retinas, retinal ganglion cell count and GFAP expression were found to correlate with cortical threshold in the ATP-injected eyes.…”
Section: Müller Cell Gliosis In the Retina Correlates To Stimulation supporting
confidence: 77%
See 2 more Smart Citations
“…Retinal ganglion cells appeared well conserved. These features are consistent with mid-to-late stage remodeling events reported in ATPinjected cat and rat retinae 24 and other models of retinal degeneration. 7,64,65 When local variations in retinal layer thickness, gliosis, and ganglion cell density were correlated with individual electrode thresholds in the implanted degenerate and control retinas, retinal ganglion cell count and GFAP expression were found to correlate with cortical threshold in the ATP-injected eyes.…”
Section: Müller Cell Gliosis In the Retina Correlates To Stimulation supporting
confidence: 77%
“…All four animals were a subset of a larger cohort (n ¼ 19) required for another study 22 Unilateral retinal degeneration was induced in all four animals by using a single intravitreal injection of ATP at a concentration of 11 mM at the retina as previously described. 22,24,25 We have previously found that ATP injection induces a global retinal degeneration with a variable pattern of photoreceptor loss, where the most severely affected inner retina occurs in regions containing fewer residual photoreceptor nuclei. 22,23 Briefly, the procedure was performed under anesthesia induced through a subcutaneous injection of ketamine (20 mg/kg; Ilium Ketamil; Troy Laboratories Pty.…”
Section: Anesthesia and Intraocular Injection Of Atpmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ATP acts as a ligand to purinergic receptors and P2X4 purinergic receptors (ionotropic receptors) are distributed in different cell types within the retina (bipolar cell terminals, horizontal cell somata and processes, calretinin-positive amacrine cells…etc), microglia, Müller cells and astrocytes. These receptors influence glia function and local tissue homeostasis in both physiological and pathological conditions (Vessey et al, 2014).…”
Section: Phagocytosismentioning
confidence: 99%
“…The posterior eyecups (n ‡ 5 per experimental group) were fixed in 4% paraformaldehyde in 0.1 M phosphate buffer, pH 7.4 (PB) for 30 minutes and cryoprotected in graded sucrose (10%, 20%, 30%) in PB overnight. 33 For retinal wholemounts, the entire eyecup (retina/choroid/sclera) was processed for immunohistochemistry as described previously 32,34 and specifically below. For retinal sections, the eyecup was embedded in optimal cutting temperature (OCT) compound (Tissue-Tek; Sakura, Torrance, CA, USA), frozen at À208C, and sectioned transversely at 14 lm on a Microm HM550 cryostat (Thermo Scientific, Walldorf, Germany).…”
Section: Immunohistochemistry and Confocal Microscopymentioning
confidence: 99%